Konsep Kemuliaan Akal Menurut Imam Al-Ghazali - Habibullah Akhul Zafa S; Khairuddin Lubis; Khairul Anwar (Fakultas Agama Islam Universitas Al Washliyah, 2025)
This research discusses the concept of nobility of reason according to Imam Al Ghazali with the main discussion being the profile of Imam Al Ghazali and what the concept of nobility of reason is according to Imam al Ghazali. This research uses qualitative research with descriptive methods and character study research. The research results show that Al-Ghaz?l?, whose full name is Abu ?amid Ibn Mu?ammad Ibn Mu?ammad Ibn A?mad al-Ghaz?l?, is a leading figure in the world of philosophy and Sufism. He has extraordinary influence and thoughts. From his intelligence in studying scientific disciplines; fiqh, kalam science, philosophy, logic, Sufism and dialectics earned him the nickname ?ujjatul Islam. Al-Ghazali divides the levels of reason into four, namely the first is the hayulani reason (material reason), this reason is useful for understanding and knowing about the fundamental material realities that exist, so to obtain the truth of this hayulani reason must go through the senses, because matter is the first reason to know more about the nature of something. Second is the instinctive reason, this reason works and functions after humans know a number of existing basic sciences. This reason seeks to know the essence behind existing realities. Efforts to find truth beyond material reality are the result of the work of the instinctive reason. Through the instinctive reason, human knowledge will advance beyond its basic knowledge and provide confidence in the truth it has obtained. Third is the active reason (actual reason), this reason functions to obtain knowledge whose truth is undoubted. This reason can know some theoretical knowledge, so that it is able to re-display known rational forms. Fourth is the mustafad reason, this reason according to al-Ghazali functions further than the previous reasons. In fact, according to al-Ghazali, this mustafad intellect is considered a high-level intellect. Al-Ghazali explained that through this intellect, humans are able to know and comprehend something and are also able to connect with the tenth intellect (the fedal intellect). The potential power of this mustafad intellect is quite substantial. In fact, it resembles the principles of mere existence.